Socio-geographical study of the quality of life of the population under contemporary conditions: the case of Chernivtsi region - Trusii, Oksana; Chubrei, Mariia-Anastasiia (Journal of Education, Health and Sport, 2026)
The article examines the theoretical and methodological foundations of the socio-geographical study of population quality of life. It substantiates their application to the analysis of Chernivtsi region as a border region characterised by pronounced internal territorial differentiation. Quality of life is interpreted as an integral socio-geographical category reflecting not only the level of material well-being of the population, but also spatially conditioned opportunities for access to basic services, security, mobility, social integration and an environmentally favourable living environment. It is argued that, under contemporary conditions of wartime transformation, increased migration mobility, growing pressure on social infrastructure, and the reorientation of regional development, the territorial organisation of society is the fundamental factor shaping the uneven distribution of quality of life. For Chernivtsi region, the key determinants include its border position, a finely dispersed settlement network, contrasts between urbanised, foothill, mountainous, and border-transit territories and the increasing role of social resilience and accessibility. The study proposes an analytical typology of intraregional territories according to the dominant parameters of quality of life. It outlines the priorities of regional policy aimed at reducing spatial disparities and enhancing the life capacity of territorial communities.